3+20x=6+92x

Simple and best practice solution for 3+20x=6+92x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+20x=6+92x equation:


3+20x=6+92x

We simplify the equation to the form, which is simple to understand
3+20x=6+92x

We move all terms containing x to the left and all other terms to the right.
+20x-92x=+6-3

We simplify left and right side of the equation.
-72x=+3

We divide both sides of the equation by -72 to get x.
x=-0.041666666666667

See similar equations:

| y=x^4-18x^2+32 | | 0.2(x+20)+0.4x=13 | | -15+n=2 | | 4(x-1)-2(3x+4)=4 | | S=1/2gt | | (12x^2y^4)(1/2x^5y) | | (2n^2)-4n+6=0 | | 59x-20=3(x+4) | | 70-4x=9-2x | | 100+20x+x^2=9900 | | 13-42=-16 | | 8x-9=2x-11 | | a-16=16 | | 1/28=1/(7x) | | 60x+30y=150 | | 6(u+3)-8u=36 | | (x+3)(x-5)=(2x+4)(x-5) | | 100+20x+X^3=9900 | | lny=19x+lnC | | x+y=13350 | | 20=20-16t^2+32t | | -4(v-2)=-4(4-8)-8v | | 10x^4-5x^3= | | 2ln(3x+8)=12 | | t-68=24 | | -4(4-2)=-4(4-8) | | 27+c=25 | | .09x+.12x=16500 | | 7z+6-2(z+3)= | | 1/3Lnx=ln7 | | H(20t)=20-16t^2+32t | | 36=j-12 |

Equations solver categories